Investigating the Effect of Service Quality, Mental Image, Trust and Environment Brand on Emotional Satisfaction and Commitment - SHIRI, Yousef Mirzaei; ALIPOOR, Vahideh; AZIMI, Hossein (Journal of Environmental Management and Tourism, 2019)
The superior service quality enables an economic unit to distinguish itself from other competitors and compared with them, gain a series of competitive advantages. Increasing the service quality will increase customer satisfaction, followed by increasing positive word of mouth (WOM), reduced staff turnover and improved financial performance of the company. The aim of this study is to find the relationship between different elements of long-term cooperation between banks and customers. The research method is a survey-descriptive research and data collection tool is a standardized questionnaire that is localized and its reliability and validity have been reaffirmed. The statistical society of this study was all customers of Tejarat, Saderat, Eghtesade Novin banks in Zanjan and the questionnaires were distributed randomly among 400 customers of these banks. The conceptual model of the research processed using the structural equation model in PLS software. Findings showed that quality of services, mental image, trust and environment brand have a positive effect on customer satisfaction and emotional commitment. Also, customer satisfaction and emotional commitment have a positive effect on behavioral tendencies.